2016
DOI: 10.1371/journal.pgen.1006003
|View full text |Cite
|
Sign up to set email alerts
|

Survival of the Curviest: Noise-Driven Selection for Synergistic Epistasis

Abstract: A major goal of human genetics is to elucidate the genetic architecture of human disease, with the goal of fueling improvements in diagnosis and the understanding of disease pathogenesis. The degree to which epistasis, or non-additive effects of risk alleles at different loci, accounts for common disease traits is hotly debated, in part because the conditions under which epistasis evolves are not well understood. Using both theory and evolutionary simulation, we show that the occurrence of common diseases (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Increased severity of deleterious mutations can lead to population-level robustness as purifying selection is more effective against strongly-deleterious mutations. It has also been proposed that increased negative (or synergistic) epistasis can evolve as a mechanism to increase the strength of purifying selection and hence robustness [26,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased severity of deleterious mutations can lead to population-level robustness as purifying selection is more effective against strongly-deleterious mutations. It has also been proposed that increased negative (or synergistic) epistasis can evolve as a mechanism to increase the strength of purifying selection and hence robustness [26,46].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the differences in the distribution of fitness effects [17] (that is, the local fitness landscapes) between fit genotypes and flat genotypes have not been explored. While it is generally assumed that mutational robustness evolves due to the evolution of an increased number of neutral mutational neighbors [18,39,41], other authors have argued that increased mutational sensitivity may evolve [3,23,26,32,46]. Additionally, recent work has indicated that populations evolving under strong genetic drift are expected to evolve "drift-robust" genetic architectures, giving rise to genotypes with a decreased likelihood of small-effect deleterious mutations and an increased likelihood of neutral and/or strongly-deleterious mutations [25].…”
Section: Introductionmentioning
confidence: 99%
“…10 On the other hand, statistical genetic evidence for a contribution of epistasis to phenotypes in higher organisms is scant, and theoretical analyses arrive at disparate conclusions regarding the significance of epistasis in complex traits and disease. 11,12 Why the results conflict is hotly debated. 13 One, uncommonly discussed reason is that the contribution of epistasis could vary with the fitness cost of a phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…13 One, uncommonly discussed reason is that the contribution of epistasis could vary with the fitness cost of a phenotype. 12 Natural selection indisputably eliminates deleterious mutations, but selection may also increase the robustness of pathways to perturbation by shaping genetic interactions and networks. 14 We reasoned that a comparative analysis of the genetic architecture of four CHD phenotypes under the same mutation could illuminate the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the differences in the distribution of fitness effects [17] (that is, the local fitness landscapes) between fit genotypes and flat genotypes have not been explored. While it is generally assumed that mutational robustness evolves due to the evolution of an increased number of neutral mutational neighbors [18,39,41], other authors have argued that increased mutational sensitivity may evolve [3,23,26,32,46]. Additionally, recent work has indicated that populations evolving under strong genetic drift are expected to evolve "drift-robust" genetic architectures, giving rise to genotypes with a decreased likelihood of small-effect deleterious mutations and an increased likelihood of neutral and/or strongly-deleterious mutations [25].…”
Section: Introductionmentioning
confidence: 99%